Forecasts with Quarterly Macroeconometric Models, Equation Adjustments, and Benchmark Predictions: The U.S. Experience - Haitovsky, Yoel; Treyz, George (The Review of Economics and Statistics, 1972)
Yoel Haitovsky, George Treyz, Forecasts with Quarterly Macroeconometric Models, Equation Adjustments, and Benchmark Predictions: The U.S. Experience, The Review of Economics and Statistics, Vol. 54, No. 3 (Aug., 1972), pp. 317-325